Characterization of human papillomavirus antibodies in individuals with head and neck cancer. (June 2016) - Lang Kuhs, Krystle A.; Pawlita, Michael; Gibson, Sandra P.; Schmitt, Nicole C.; Trivedi, Sumita; Argiris, Athanassios; Kreimer, Aimée R.; Ferris, Robert L.; Waterboer, Tim
Highlights: We tested 260 incident head and neck cancers for HPV antibodies. 63.2% of OPC and 27.5% non-OPC cases were seroreactive against HPV16 proteins. HPV16 E6 antibodies were most common, 60.5% and 6.3% for OPC versus non-OPC. A subset of cases had known HPV status (N = 25). 100% (N = 6) and 0% (N = 2) of HPV-driven OPC and non-OPC cases had E6 antibodies Abstract: Background: Human papillomavirus type 16 (HPV16) E6 antibodies are a promising biomarker of oropharyngeal cancer (OPC); however, seropositivity among non-OPC cases is not well characterized. Methods: Pre-treatment sera from 260 (38 OPC, 222 non-OPC) incident head and neck cancers diagnosed at the University of Pittsburgh between 2003 and 2006 were tested for HPV16 (L1, E1, E2, E4, E6, E7) and non-HPV16 E6 (HPV6, 11, 18, 33) antibodies. Sensitivity and specificity of HPV16 E6 antibodies for HPV-driven tumors was evaluated among tumors with known HPV status (n = 25). Results: 63.2% of OPC versus 27.5% of non-OPC cases were HPV16 seropositive; HPV16 E6 seroprevalence was 60.5% and 6.3% respectively, odds ratio 22.8 (95% confidence interval [CI] 9.8–53.1). Sensitivity and specificity of HPV16 E6 antibodies for HPV-driven OPC was 100% [95% CI: 50–100%; n = 6] and 100% [95% CI: 60–100%, n = 4] compared to 0% (n = 2) and 0% (n = 13) for non-OPC cases. Conclusions: HPV16 antibodies were significantly more common in OPC versus non-OPC cases, particularly HPV16 E6 antibodies.